2000
DOI: 10.1051/aas:2000160
|View full text |Cite
|
Sign up to set email alerts
|

Surface photometry of emission-line galaxies in low density regions

Abstract: Abstract. Detailed B and R surface photometry is performed for 139 faint emission-line galaxies (ELGs) and for 2 non-ELGs. They are a subsample of the ELG sample selected by Popescu et al. (1996Popescu et al. ( , 1998 towards four nearby voids. We derived the isophotal and integral photometric parameters and radial surface brightness (SB) profiles. Our sample consists mostly of low luminosity (< M B > med = −17.7), small linear size (< d 25 > med = 6.0 kpc) (H 0 = 75 km s −1 Mpc −1 ) and blue (< B−R > med = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
7
21
0
Order By: Relevance
“…Previous optical studies (e.g. LT86, P96a, Telles et al 1997;Marlowe et al 1997;Salzer & Norton 1999;Vennik et al 2000;Cairós et al 2001aCairós et al , 2001bMakarova et al 2002) of BCDs suggest that those systems mostly show no strong deviations from an exponential law over their outer LSB SBPs. Also if small deviations from an exponential law which are hardly detectable in current data should exist, a med gives a robust approximation by fixing the LSB profile shape.…”
Section: The Sérsic Law Vs the Med For Studies Of Type V Sbpsmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous optical studies (e.g. LT86, P96a, Telles et al 1997;Marlowe et al 1997;Salzer & Norton 1999;Vennik et al 2000;Cairós et al 2001aCairós et al , 2001bMakarova et al 2002) of BCDs suggest that those systems mostly show no strong deviations from an exponential law over their outer LSB SBPs. Also if small deviations from an exponential law which are hardly detectable in current data should exist, a med gives a robust approximation by fixing the LSB profile shape.…”
Section: The Sérsic Law Vs the Med For Studies Of Type V Sbpsmentioning
confidence: 89%
“…Binggeli & Cameron 1991;Cellone et al 1994;Young & Currie 1994, and Vennik et al (2000) deduce a fraction of >10% for the SBPs of late-type dwarf galaxies falling into this category. In fact, a casual inspection of the sample of Patterson & Thuan (1996), Makarova et al (1998), Vennik et al (2000) and van Zee (2000) (Duc et al 1999) and Kar 50 (Davidge 2002). Following the nomenclature of Binggeli & Cameron (1991) we shall henceforth refer to this type of SBPs as to type V.…”
Section: Profile Decompositionmentioning
confidence: 93%
See 1 more Smart Citation
“…Popescu et al (1999) reported no conspicuous difference in present and past SF activity for ELGs in field and void environments. On the other hand, Vennik et al (2000) found that the low surface brightness hosts of non-isolated ELGs tend to be more compact than those of isolated ones.…”
Section: Introductionmentioning
confidence: 95%
“…Objects referred to have precise B-magnitude in Vennik, et al (2000). We do not list them here for the sake of homogeneity.…”
Section: Emission-line Galaxiesmentioning
confidence: 99%